Poor Prognosis of Intraoperative Rupture of Mature Cystic Teratoma with Malignant Transformation - Kuo-Chang Wen; Wei-Ming Hu; Nae-Fang Twu; Pwu Chen; Peng-Hui Wang (Elsevier, 2006)
Objective: To present the phenomenon of the postoperative rapid progression of mature cystic teratoma (MCT) with malignant transformation (MT) when intraoperative spillage occurs during operation. Case Report: Two patients with MCT were treated, one with total hysterectomy plus bilateral salpingooophorectomy in an exploratory laparotomy, and the other with cystectomy with laparoscopy, respectively. Tumor spillage occurred during both operations. The postoperative pathology showed MCT with MT (squamous cell carcinoma type). Both patients were referred to our hospital and underwent treatment (3 months and 8 days, respectively, after the initial operation). At the secondary laparotomy for staging surgery, tumor dissemination was observed in both patients. Conclusion: Whether or not tumor dissemination is correlated with tumor rupture during operation, we emphasize that any patient with a preoperative diagnosis of MCT should have it removed intact to avoid the possibly catastrophic event of tumor dissemination.